PAK Pengaruh Seks Pranikah Terhadap Keharmonisan Dalam Keluarga - Yanty Piri; Kalis Stevanus; David Priyo Susilo; Fianus Tandiongan (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2022)
Marriage is a place that God has ordained for married couples to express their sexual life. Premarital sex is a form of violation of God's decree. This study aims to determine how much influence premarital sex behavior on harmony in the family at GBT Christ Alfa Omega Semarang. To answer the research objectives, the researcher used correlational quantitative research by taking a sample of 35 people who had attended premarital counseling and were married. The results of the study found that the variable X (premarital sex) had an effect on the variable Y (family harmony) in the medium category. However, the results of the linearity test showed that the data was not linear, so the correlational hypothesis test using a nonparametric test showed that there was no significant effect between premarital sex on harmony in the family after following premarital guidance.